2022
DOI: 10.3390/ma15175985
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Titanium Sheet Metal Using Laser Metal Deposition to Improve Room Temperature Single-Point Incremental Forming

Abstract: Typically, due to their limited formability, elevated temperatures are required in order to achieve complex shapes in titanium alloys. However, there are opportunities for forming such alloys at room temperature using incremental forming processes such as single-point incremental forming (SPIF). SPIF is an innovative metal forming technology which uses a single tool to form sheet parts in place of dedicated dies. SPIFs ability to increase the forming limits of difficult-to-form materials offers an alternative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…The study showed that the shape of the retaining rings significantly influenced the final geometric accuracy of the parts produced by ISF. A novel method was presented by McPhillimy et al (2022). The authors applied laser metal deposition to thicken locally titanium grade 2 sheet before incremental forming process.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that the shape of the retaining rings significantly influenced the final geometric accuracy of the parts produced by ISF. A novel method was presented by McPhillimy et al (2022). The authors applied laser metal deposition to thicken locally titanium grade 2 sheet before incremental forming process.…”
Section: Introductionmentioning
confidence: 99%
“…McPhillimy et al [4] generated a laser metal deposition tailored preform with a variable thickness to mitigate thinning, a common defect in the room temperature singlepoint incremental forming (SPIF) of titanium parts with high angled walls. An initial material study of a laser metal deposition (LMD) tailored CP-Ti50A sheet with localized thickening was performed.…”
mentioning
confidence: 99%